Reading Paul from the Margins - Nicolet, Valérie (Early christianity, 2024)
The article reflects on the possibilities of combining critical and historical approaches to read Paul. This methodological perspective aims to include the experiences of people who were perceived as second-class persons in the ancient world (people like women, slaves, children, non-Roman citizens, also known as barbarians) and to avoid a universalizing approach to the Pauline material. A historical approach tries to reconstruct how Paul's thought would have resonated for people in the first century and needs to be informed by critical approaches to remind historians to think of the diversity of the people in the ancient world. I will use two examples, one coming from Romans and the other from Galatians, to show how Paul's good news can be read as what Lauren Berlant calls "cruel optimism"1 when it is addressed to people deprived of the privileges that Roman citizenship, maleness, money, education, and freedom afforded to a small elite class. I will conclude these reflections by developing our responsibility as interpreters: how do we use our travels through history, to distant lands, in distant times, among distant people, to inform our thinking today? To say it differently, how do we, as readers of ancient texts, respond to the hermeneutical need?